2010
DOI: 10.1002/pssc.201000094
|View full text |Cite
|
Sign up to set email alerts
|

Gold electrodeposition into porous silicon: Comparison between meso‐ and macroporous silicon

Abstract: We report the fabrication and characterization of porous Si templates for electrodeposition of Au high aspect ratio nanostructures. The templates with ordered and controlled pore size, 4 µm and 50 nm in diameter, were created through Si etching. Electrodeposition of Au into macroporous Si and into mesoporous Si was investigated. The different morphologies of deposits depending on the Si type and pore size were compared and discussed. The morphology and structural characteristic of the fabricated nanostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Figure shows the UV–vis spectra recorded with linearly polarized light for two azimuthal orientations of the films defined along the bundling direction in the plasma assisted OAD films (0° polarization) or the perpendicular to it (90° polarization). For these two orientations, the spectra of the evaporated ITO films depict a similar absorption band at 535 nm attributed to the surface plasmon resonance of the electrochemically deposited gold nanoparticles. ,,, Conversely, in the plasma assisted film, azimuthally turning the sample leads to significant changes in the absorption spectra. At 0°, the spectrum is characterized by a well-defined resonance peak at 520 nm, whereas at 90° it depicts a less resolved structure where two broad and little resolved bands at 580 and 700 nm can be seen.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure shows the UV–vis spectra recorded with linearly polarized light for two azimuthal orientations of the films defined along the bundling direction in the plasma assisted OAD films (0° polarization) or the perpendicular to it (90° polarization). For these two orientations, the spectra of the evaporated ITO films depict a similar absorption band at 535 nm attributed to the surface plasmon resonance of the electrochemically deposited gold nanoparticles. ,,, Conversely, in the plasma assisted film, azimuthally turning the sample leads to significant changes in the absorption spectra. At 0°, the spectrum is characterized by a well-defined resonance peak at 520 nm, whereas at 90° it depicts a less resolved structure where two broad and little resolved bands at 580 and 700 nm can be seen.…”
Section: Resultsmentioning
confidence: 94%
“…For these two orientations, the spectra of the evaporated ITO films depict a similar absorption band at 535 nm attributed to the surface plasmon resonance of the electrochemically deposited gold nanoparticles. 50,51,64,65 Conversely, in the plasma assisted film, azimuthally turning the sample leads to significant changes in the absorption spectra. At 0°, the spectrum is characterized by a well-defined resonance peak at 520 nm, whereas at 90°it depicts a less resolved structure where two broad and little resolved bands at 580 and 700 nm can be seen.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 99%
“…This is due to the fast rate of displacement deposition. In previous papers, we have reported that the displacement deposition of gold is suppressed by controlling the solution composition [ 18 , 19 ]. The reason why the displacement deposition is suppressed has been reported elsewhere [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous papers, we have reported that the displacement deposition of gold is suppressed by controlling the solution composition [ 18 , 19 ]. The reason why the displacement deposition is suppressed has been reported elsewhere [ 18 ]. Here, we also use the aqueous solution, which can inhibit the displacement deposition of gold, containing HAuCl 4 , Na 2 SO 3 and Na 2 S 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the valence band is located at the same energy level as the Fermi level making the substrate neutral toward the energy level of the metallic redox couple. In another report, we have shown that Au deposits start to grow mainly from the pore bottom when we use Na 2 S 2 O 3 and Na 2 SO 3 for the preparation of the Au ion solution (14). However, when we used NaCl deposition occurs mainly on the top surface.…”
Section: Discussionmentioning
confidence: 96%